2006
DOI: 10.1002/job.387
|View full text |Cite
|
Sign up to set email alerts
|

Team mental models and team performance: a field study of the effects of team mental model similarity and accuracy

Abstract: SummaryWe conducted a field study of 71 action teams to examine the relationship between team mental model similarity and accuracy and the performance of real-world teams. We used Pathfinder to operationalize team members' taskwork mental models (describing team procedures, tasks, and equipment) and teamwork mental models (describing team interaction processes) and examined team performance as evaluated by expert team assessment center raters. Both taskwork mental model and teamwork mental model similarity pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
488
4
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 476 publications
(511 citation statements)
references
References 28 publications
10
488
4
9
Order By: Relevance
“…Although significant research has focused on exploring the potential benefits of these two cognitions on outcomes such as team performance and satisfaction (e.g., Austin, 2003;Edwards, Day, Arthur, & Bell, 2006;Ellis, 2006;Lewis, 2003;Pearsall & Ellis, 2006) as well as identifying their potential antecedents (e.g., Marks, Zaccaro, & Mathieu, 2000;Marks, Sabella, Burke, & Zaccaro, 2002), the processes and developmental phases underlying their emergence in newly formed teams have yet to be explored (e.g., Ilgen et al, 2005;Kozlowski & Bell, 2003;Lim & Klein, 2006;Mohammed & Dumville, 2001). It is clear that shared cognition does not develop automatically; it requires team members to engage in purposeful interpersonal interactions directed towards understanding their teammates' roles and capabilities (see Kozlowski, Gully, Nason & Smith, 1999;Lewis, Lange, & Gillis, 2005).…”
Section: Team Cognition Developmentmentioning
confidence: 99%
“…Although significant research has focused on exploring the potential benefits of these two cognitions on outcomes such as team performance and satisfaction (e.g., Austin, 2003;Edwards, Day, Arthur, & Bell, 2006;Ellis, 2006;Lewis, 2003;Pearsall & Ellis, 2006) as well as identifying their potential antecedents (e.g., Marks, Zaccaro, & Mathieu, 2000;Marks, Sabella, Burke, & Zaccaro, 2002), the processes and developmental phases underlying their emergence in newly formed teams have yet to be explored (e.g., Ilgen et al, 2005;Kozlowski & Bell, 2003;Lim & Klein, 2006;Mohammed & Dumville, 2001). It is clear that shared cognition does not develop automatically; it requires team members to engage in purposeful interpersonal interactions directed towards understanding their teammates' roles and capabilities (see Kozlowski, Gully, Nason & Smith, 1999;Lewis, Lange, & Gillis, 2005).…”
Section: Team Cognition Developmentmentioning
confidence: 99%
“…Previous research has shown that the components of a group's mental model about the task may include understanding of the nature of the problem; the task(s) and subtasks; task-related constraints; strategies, procedures, or contingencies; and measures of success of failure (Cannon-Bowers, et al, 1993;Klimoski & Mohammed, 1994;Lim & Klein, 2006;Rentsch & Woehr, 2004). The interview protocol elicited information about these elements, and they were used as the basis for content analysis of responses.…”
Section: Task Mental Modelmentioning
confidence: 99%
“…Shared team mental models are important for performance particularly in contexts where teams have very little time for explicit coordination. For example, a shared understanding of an emerging situation helps military action teams take appropriate, efficient collective action (Lim & Klein, 2006). Shared mental models are also important in contexts where team members have to collaborate on a complex task, such as strategic decision-making in top management teams (Ensley & Pearce, 2001).…”
Section: Introductionmentioning
confidence: 99%